Acceptance and use of lecture capture system (LCS) in executive business studies - Muhammad Shoaib, Farooq; Maimoona, Salam; Norizan, Jaafar; Fayolle, Alain; Kartinah, Ayupp; Radovic-Markovic, Mirjana; Sajid, Ali (Emerald Publishing Limited, 2017)
Adoption of latest technological advancements (e.g. lecture capture system) is a hallmark of market-driven private universities. Among many other distinguishing features, lecture capture system (LCS) is the one which is being offered to enhance the flexibility of learning environment for attracting executive business students. Majority of foreign universities are offering the facility of LCS to their students in offshore campuses established in Malaysia. Yet, very little is known about perception and behaviour of executive business students towards acceptance and use of this facility. Therefore, to bridge the identified gap in academic literature, this study is an effort to explore the causal relationship between existing constructs of extended unified theory of acceptance and use of technology (UTAUT2), personal innovativeness (PI), intention and use behaviour (UB) towards LCS. Moreover, this study is aimed to extend the UTAUT2 by introducing a new variable, namely, PI in the domain of information technology (IT) (PIIT).